New insights into dissociation of deprotonated 2, 4‐dinitrotoluene by combined high‐resolution mass spectrometry and density functional theory calculations. (15th January 2015) - Schwarzenberg, Adrián; Tabet, Jean‐Claude; Cole, Richard B.; Machuron‐Mandard, Xavier; Dossmann, Héloïse
<x xml:space="preserve">Abstract</x> RATIONALE 2, 4‐Dinitrotoluene (2, 4‐DNT) is a nitroaromatic explosive which is commonly found in environmental samples close to training points, firing places, and manufacturers. Mass spectrometry analysis of this compound shows one main product ion that distinguishes it from the other isomers of DNT. We present here a detailed mechanistic study on the formation of this ion. METHODS 2, 4‐DNT was analyzed using negative electrospray ionization high‐resolution mass spectrometry (ESI‐HRMS) using a linear ion trap quadrupole LTQ‐Orbitrap XL mass spectrometer. Collision‐induced dissociation (CID) experiments were performed on the [M–H]– ion obtained. Density functional theory (DFT) calculations were used to support experimental observations. RESULTS Fragmentation of deprotonated 2, 4‐DNT [M–H]– (m/z 181) yields a main product ion at m/z 116. The mechanism of formation of this diagnostic product ion is not obvious and it has never been rationalized. Calculations were performed to probe different mechanistic variants, which are discussed in this work. CONCLUSIONS Analysis of possible pathways to form the m/z 116 ion from the m/z 181 precursor shows that its formation is likely to proceed first via NO loss, followed by eliminations of H2O and then HO. Copyright © 2014 John Wiley & Sons, Ltd.